Ambient air pollution and risk of respiratory infection among adults: evidence from the multiethnic study of atherosclerosis (MESA) - Kirwa, Kipruto (BMJ Open Respir Res, 2021)
BACKGROUND: Air pollution may affect the risk of respiratory infection, though research has focused on uncommon infections or infections in children. Whether ambient air pollutants increase the risk of common acute respiratory infections among adults is uncertain, yet this may help understand whether pollutants influence spread of pandemic respiratory infections like COVID-19. OBJECTIVE: To estimate the association between ambient air pollutant exposures and respiratory infections in adults. METHODS: During five study examinations over 12 years, 6536 participants in the multiethnic study of atherosclerosis (MESA) reported upper respiratory tract infections, bronchitis, pneumonia or febrile illness in the preceding 2 weeks. Using a validated spatiotemporal model, we estimated residential concentrations of ambient PM(2.5), NO(x) and NO(2) for the 2–6 weeks (short-term) and year (long-term) prior to each examination. RESULTS: In this population aged 44–84 years at baseline, 10%–32% of participants reported a recent respiratory infection, depending on month of examination and study region. PM(2.5), NO(x) and NO(2) concentrations over the prior 2–6 weeks were associated with increased reporting of recent respiratory infection, with risk ratios (95% CIs) of 1.04 (1.00 to 1.09), 1.15 (1.10 to 1.20) and 1.21 (1.10 to 1.33), respectively, per increase from 25th to 75th percentile in residential pollutant concentration. CONCLUSION: Higher short-term exposure to PM(2.5) and traffic-related pollutants are associated with increased risk of symptomatic acute respiratory infections among adults. These findings may provide an insight into the epidemiology of COVID-19.